A super-tough epoxy steel slag asphalt mixture and preparation method thereof
By adding modified epoxy resin and fiber to the epoxy asphalt material, an ultra-tough epoxy steel slag asphalt mixture was prepared, which solved the problem of insufficient toughness of epoxy asphalt in low-temperature environments, and significantly improved its low-temperature crack resistance and water stability.
Patent Information
- Application Number
- CN202311129805.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Epoxy asphalt is not tough enough in low-temperature environments, resulting in brittle damage and cracks under load, which affects the service life.
The preparation method of ultra-tough epoxy steel slag asphalt mixture, including basalt aggregate, steel slag coarse aggregate, ore powder filler, SBS modified asphalt, fiber and modified epoxy resin, is used to prepare epoxy asphalt materials with higher and lower temperature crack resistance through specific ratios and process steps.
It significantly improves the low-temperature strength and deformation ability of epoxy asphalt materials, effectively improves its crack resistance in low-temperature environments, and improves water stability and fatigue resistance, extending the service life of the road surface.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of asphalt materials, and particularly relates to a super-tough epoxy steel slag asphalt and a preparation method thereof. Background Art
[0002] With the rapid development of my country's transportation sector, the scale of road projects has expanded rapidly, the road grade has generally improved, and the increase in traffic volume has made the requirements for road construction more stringent. Epoxy resin has good processability and adhesion, low shrinkage, and excellent chemical corrosion resistance and heat resistance. The prepared epoxy modified asphalt has the advantages of high strength, good high temperature stability, fatigue resistance and strong corrosion resistance. However, the addition of epoxy resin will reduce the flexibility of asphalt, and the strength of the cured epoxy asphalt mixture will increase while the flexibility will decrease. Under low temperature conditions, the plastic deformation capacity of the mixture is poor, and brittle failure is prone to occur under load, resulting in cracks and other diseases on the road surface, which in turn affects the service life. Therefore, improving the flexibility of epoxy asphalt concrete has become an urgent problem to be solved. Highway construction also requires a large amount of natural stone, a large amount of transportation costs, and traditional coarse aggregate resources are scarce. Steel slag is a by-product of steelmaking, and its production accounts for 10-20% of crude steel production. As an industrial waste, it has its unique advantages in road construction. Steel slag has sharp edges and corners, is hard, has good mechanical properties, is anti-slip and wear-resistant, and has low cost. Using steel slag to build roads can also improve the resource utilization rate of steel slag and protect the ecological environment. Summary of the invention
[0003] Purpose of the invention: The technical problem to be solved by the present invention is that the low-temperature toughness of epoxy asphalt is insufficient. In order to improve the problem that epoxy asphalt steel slag concrete is prone to cracking in low-temperature environments, a method for preparing an ultra-tough epoxy asphalt mixture is provided to prepare epoxy asphalt materials with better road performance and better low-temperature crack resistance.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] An ultra-tough epoxy steel slag asphalt mixture comprises the following components by weight: 61-71 parts of basalt aggregate, 33-38 parts of steel slag coarse aggregate, 1-2 parts of mineral powder filler, 4-5 parts of SBS modified asphalt, 0.4-0.6 parts of fiber, and 4-8 parts of modified epoxy resin;
[0006] Wherein, the modified epoxy resin is prepared by the following steps:
[0007] S1: Mix chlorogenic acid, allyl alcohol glycidyl ether and water evenly, then add sodium hydroxide, stir evenly, and place in a four-necked flask equipped with a mechanical stirrer, a condenser, a thermometer sleeve and a nitrogen inlet;
[0008] S2: introduce nitrogen into the four-necked flask and start stirring, heat to 95-105°C and react for 24-26 hours;
[0009] S3: After the reaction is completed, the product is cooled to room temperature and dialyzed to remove unreacted allyl alcohol glycidyl ether, and water is removed by rotary evaporation to obtain an epoxy resin modifier;
[0010] S4: Mix the epoxy resin modifier obtained by the reaction with the epoxy resin, heat to 55-65° C. and mechanically stir for 6-8 minutes;
[0011] S5: Add epoxy resin curing agent to the product of step S4, and continue stirring at 55-65° C. for 4-6 min to obtain the product.
[0012] Specifically, the basalt aggregate includes basalt No. 1 material with a particle size of 10-15mm, basalt No. 2 material with a particle size of 5-10mm, and basalt No. 3 material with a particle size of 0-5mm; the mass ratio of basalt No. 1 material, basalt No. 2 material, and basalt No. 3 material is 14-17:9-12:38-42.
[0013] Specifically, the steel slag coarse aggregate is converter steel slag or electric furnace steel slag, including steel slag No. 1 material with a particle size of 10-15mm and steel slag No. 2 material with a particle size of 5-10mm, and the mass ratio of steel slag No. 1 material to steel slag No. 2 material is 20-22:13-16.
[0014] Specifically, the particle size of the mineral powder filler is not greater than 6 mm.
[0015] Specifically, the SBS modified asphalt type is any one of type IA, type IB, type IC or type ID.
[0016] Specifically, the fiber is basalt fiber or lignin fiber.
[0017] Specifically, in step S1, the mass ratio of chlorogenic acid, allyl alcohol glycidyl ether and water is 2-3:32-35:64-68; and the added amount of sodium hydroxide is 0.5-0.7% of the mass of allyl alcohol glycidyl ether.
[0018] Specifically, in step S4, the epoxy resin is bisphenol A epoxy resin; the mass ratio of the epoxy resin modifier to the epoxy resin is 2-4:96-98.
[0019] Specifically, in step S5, the epoxy resin curing agent is polyamide 651, and the mass ratio of the epoxy resin curing agent to the product of step S4 is 35-50:50-65.
[0020] Furthermore, the present invention also provides a method for preparing the above-mentioned super-tough epoxy steel slag asphalt mixture, comprising the following steps:
[0021] (1) Heat and stir basalt aggregate, steel slag coarse aggregate and fiber to mix them evenly;
[0022] (2) Heat the SBS modified asphalt to 170-180°C for use;
[0023] (3) adding the modified epoxy resin to the SBS modified asphalt prepared in step (2) and stirring the mixture sufficiently to prepare epoxy asphalt for later use;
[0024] (4) Pour the epoxy asphalt prepared in step (3) into a mixing pot preheated to 165-175°C, heat and stir for 80-90 seconds, then add the mineral powder filler and stir thoroughly;
[0025] (5) The mixture obtained in step (1) and the mixture obtained in step (4) are mixed and stirred evenly, and then cured at 165-175°C to obtain the mixture. Beneficial Effects
[0026] (1) The present invention adds steel slag to the coarse aggregate, which can apply industrial waste to road construction and solve the problems of environmental pollution and aggregate shortage. Since steel slag contains minerals such as iron and manganese, the crushing value and abrasion value of steel slag coarse aggregate are lower than those of ordinary limestone coarse aggregate. The angularity and porosity of steel slag itself enhance the friction and interlocking effect of the mixture, thereby improving the service life and skid resistance of the road surface. The surface of steel slag is porous and alkaline, which makes the adhesion between steel slag aggregate and asphalt good. Epoxy asphalt has high strength, good fatigue resistance and corrosion resistance, which will effectively reduce the occurrence of road surface diseases.
[0027] (2) After curing, the epoxy resin of the present invention will cross-link in the asphalt to form a stable network structure, effectively improving the high-temperature stability of the epoxy asphalt steel slag concrete. In addition, the fiber can absorb more free asphalt, increase the viscosity and cohesion of the asphalt, further improve the high-temperature stability, and meet the anti-rutting requirements.
[0028] (3) The present invention uses epoxy resin modifiers to toughen epoxy resin. The addition of epoxy resin modifiers can change the rigid benzene ring structure contained in the epoxy resin and the highly cross-linked three-dimensional network structure formed after curing, so that the epoxy cured product produces microphase separation, thereby achieving the purpose of improving toughness. In addition, the modifier can weaken the interaction between polymer molecules to a certain extent, thereby enhancing the mobility between polymer molecules, significantly improving the tensile strength and elongation at break of epoxy asphalt, and greatly improving the flexibility compared with ordinary epoxy asphalt.
[0029] (4) Compared with ordinary epoxy asphalt steel slag mixture, the low-temperature strength and low-temperature deformation capacity of the epoxy asphalt steel slag mixture modified by the modifier in the present invention are significantly improved, which can effectively improve the problem of easy cracking in low-temperature environment. At the same time, the water stability and fatigue resistance of the modified epoxy asphalt steel slag mixture are greatly improved. DETAILED DESCRIPTION
[0030] The present invention can be better understood with reference to the following examples. Example 1
[0031] The formula of this embodiment is as follows: 16 parts of basalt No. 1 material, 10 parts of basalt No. 2 material, 40 parts of basalt No. 3 material, 20 parts of steel slag No. 1 material, 13 parts of steel slag No. 2 material, 4 parts of SBS modified asphalt, 1 part of mineral powder filler, 0.4 parts of basalt fiber, and 4 parts of modified epoxy resin (wherein the mass ratio of chlorogenic acid (CA), allyl alcohol glycidyl ether (AGE) and deionized water in the epoxy resin modifier raw material is 2:33:65).
[0032] The epoxy resin modification process of the present invention comprises the following steps:
[0033] S1: Take chlorogenic acid (CA), allyl alcohol glycidyl ether (AGE) and deionized water in a mass ratio of 2:33:65, add a small amount of sodium hydroxide (0.5% of the mass of AGE), and place in a four-necked flask with mechanical stirring, condenser, thermometer sleeve and nitrogen inlet;
[0034] S2: nitrogen was introduced and stirring was started (600 r / min). After 25 min, the mixture was heated to 100 °C and reacted for 24 h.
[0035] S3: After the reaction is completed, the product is cooled to room temperature and dialyzed to remove unreacted AGE, and the water is removed by rotary evaporation;
[0036] S4: The reaction product (i.e., epoxy resin modifier) and epoxy resin are mixed in proportion, heated to 60°C and mechanically stirred for 6 min;
[0037] S5: Add the calculated amount of epoxy resin curing agent and continue stirring at 60°C for 4 min.
[0038] Furthermore, the ultra-tough epoxy asphalt and the steel slag asphalt mixture thereof are prepared by the following method:
[0039] (1) Weigh basalt aggregate, steel slag coarse aggregate and basalt fiber according to the mass ratio, heat and stir the three for 90 seconds for later use;
[0040] (2) Heat the SBS modified asphalt to 170°C for use;
[0041] (3) Add the modified epoxy resin into the SBS modified asphalt according to the mass ratio and stir for 10 minutes to prepare epoxy asphalt for use;
[0042] (4) Weigh epoxy asphalt according to the mass ratio and pour it into a preheated 170℃ mixing pot and heat and stir for 90 seconds for later use;
[0043] (5) Weigh the mineral powder filler according to the mass ratio and pour it into a preheated 170℃ mixing pot and heat and stir for 90 seconds for later use;
[0044] (6) Place the mixture in a 170°C oven. Example 2
[0045] The difference from Example 1 is that 4 parts of modified epoxy resin are used (wherein the mass ratio of chlorogenic acid (CA), allyl alcohol glycidyl ether (AGE) and deionized water in the epoxy resin modifier raw material is 3:31:66).
[0046] The preparation method is the same as that of Example 1. Example 3
[0047] The difference from Example 1 is that 4 parts of modified epoxy resin are used (wherein the mass ratio of chlorogenic acid (CA), allyl alcohol glycidyl ether (AGE) and deionized water in the epoxy resin modifier raw material is 4:32:64).
[0048] The preparation method is the same as that of Example 1. Example 4
[0049] The difference from Example 1 is that there are 12 parts of basalt No. 1 material, 8 parts of basalt No. 2 material, 41 parts of basalt No. 3 material, 22 parts of steel slag No. 1 material, and 16 parts of steel slag No. 2 material.
[0050] The preparation method is the same as that of Example 1.
[0051] Comparative Example 1
[0052] The difference from Example 1 is that no steel slag is added, 36 parts of basalt No. 1 material and 23 parts of basalt No. 2 material are used.
[0053] The preparation method is the same as that of Example 1.
[0054] Comparative Example 2
[0055] The difference from Example 1 is that the epoxy resin is not modified.
[0056] The preparation method is the same as that of Example 1.
[0057] Comparative Example 3
[0058] The difference from Example 1 is that there are 12 parts of basalt No. 1 material, 8 parts of basalt No. 2 material, 41 parts of basalt No. 3 material, 22 parts of steel slag No. 1 material, 16 parts of steel slag No. 2 material, and no epoxy resin modifier is added.
[0059] The preparation method is the same as that of Example 1.
[0060] According to the plastic tensile property determination method (ASTM D638), epoxy asphalt was molded into dumbbell-shaped specimens, and the tensile strength and elongation at break of toughened epoxy asphalt were tested using a universal testing machine. According to the "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011), the performance of steel slag asphalt mixture was tested using freeze-thaw splitting test, immersion Marshall test, and low-temperature bending test. The test results of each embodiment and comparative example are shown in Table 1.
[0061] Table 1
[0062]
[0063] From the comparative analysis in Table 1, we can see that:
[0064] (1) By comparing Example 1, Example 2, Example 3, and Example 4, it can be seen that the proportions of the components of the modifier proposed by the present invention are relatively reasonable, and the proportion of the raw materials in the epoxy resin modifier has little effect on the experimental results. The road performance of epoxy asphalt and its steel slag asphalt mixture within the given component ratio range has been greatly improved.
[0065] (2) By comparing Example 1 with Comparative Example 1, it can be seen that under the same coarse aggregate dosage conditions, the performance indicators of the mixture obtained by the solution of using modified steel slag instead of basalt as coarse aggregate proposed in the present invention are not much different from those of the basalt asphalt mixture, and its comprehensive road performance such as low-temperature crack resistance and water stability all meet the requirements of the specifications.
[0066] (3) By comparing Example 1 with Comparative Examples 2 and 3, it can be seen that after the epoxy resin modifier is added to the epoxy asphalt, its tensile strength becomes higher, the elongation at break becomes larger, and the toughness of the epoxy asphalt is greatly improved. Under the same coarse aggregate dosage conditions, after the epoxy resin modifier is added to the steel slag asphalt mixture, its flexural tensile strain becomes larger and the flexural tensile strength becomes higher, indicating that the toughness and low-temperature performance of the steel slag asphalt mixture modified by the epoxy asphalt modifier are greatly improved compared with the steel slag asphalt mixture prepared in the comparative example, and the TSR and residual stability are both increased, indicating that the water stability of the modified mixture is improved to a certain extent.
[0067] (4) By comparing Example 1 with Comparative Examples 1, 2 and 3, it can be seen that the toughness, water stability and low temperature performance of the steel slag asphalt mixture obtained by modification with the epoxy resin modifier are greatly improved, and all meet the requirements of the specification. Steel slag can replace natural aggregates, and the surface of steel slag aggregates is porous and alkaline, which makes the adhesion between steel slag aggregates and asphalt good, improves the road performance of the mixture, and has great significance for reducing costs, saving resources and promoting ecological civilization construction.
[0068] (5) The epoxy resin is toughened by using epoxy resin modifiers. The addition of epoxy resin modifiers can change the rigid benzene ring structure contained in the epoxy resin and the highly cross-linked three-dimensional network structure formed after curing, so that the epoxy cured product produces microphase separation, thereby achieving the purpose of improving toughness and maintaining its strength and modulus. The addition of modifiers also changes the composition of epoxy asphalt, increases the proportion of light components, thereby improving the interaction between polymer molecules, enhancing the mobility between molecules, and improving its ductility, effectively solving the current problem of insufficient low-temperature toughness of epoxy asphalt.
[0069] (6) Compared with ordinary epoxy asphalt steel slag mixture, the low-temperature strength and low-temperature deformation capacity of the epoxy asphalt steel slag mixture modified by the modifier are significantly improved, which can effectively solve the problem of easy cracking in low temperature environment. At the same time, the water stability and fatigue resistance of the modified epoxy asphalt steel slag mixture are greatly improved.
[0070] The present invention provides a super-tough epoxy steel slag asphalt mixture and a method for preparing the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. A super-tough epoxy steel slag asphalt mixture, characterized in that: The invention comprises the following components in parts by weight: 61-71 parts of basalt aggregate, 33-38 parts of steel slag coarse aggregate, 1-2 parts of mineral powder filler, 4-5 parts of SBS modified asphalt, 0.4-0.6 parts of fiber, and 4-8 parts of modified epoxy resin; The super-tough epoxy steel slag asphalt mixture is prepared by the following steps, including the following steps: (1) Heat and stir basalt aggregate, steel slag coarse aggregate and fiber to mix them evenly; (2) Heat the SBS modified asphalt to 170-180°C for use; (3) adding the modified epoxy resin to the SBS modified asphalt prepared in step (2) and stirring the mixture sufficiently to prepare epoxy asphalt for later use; (4) Pour the epoxy asphalt prepared in step (3) into a mixing pot preheated to 165-175°C, heat and stir for 80-90 seconds, then add the mineral powder filler and stir thoroughly; (5) The mixture obtained in step (1) and the mixture obtained in step (4) are mixed and stirred evenly, and then cured at 165-175° C. to obtain the mixture; Wherein, the modified epoxy resin is prepared by the following steps: S1: Mix chlorogenic acid, allyl alcohol glycidyl ether and water evenly, then add sodium hydroxide, stir evenly, and place in a four-necked flask equipped with a mechanical stirrer, a condenser, a thermometer sleeve and a nitrogen inlet; S2: introduce nitrogen into the four-necked flask and start stirring, heat to 95-105°C and react for 24-26 h; S3: After the reaction is completed, the product is cooled to room temperature and dialyzed to remove unreacted allyl alcohol glycidyl ether, and water is removed by rotary evaporation to obtain an epoxy resin modifier; S4: Mix the epoxy resin modifier obtained by the reaction with the epoxy resin, heat to 55-65°C and mechanically stir for 6-8 minutes; S5: Add epoxy resin curing agent to the product of step S4, and continue stirring at 55-65° C. for 4-6 minutes to obtain; In step S1, the mass ratio of chlorogenic acid, allyl alcohol glycidyl ether and water is 2-3:32-35:64-68; the amount of sodium hydroxide added is 0.5-0.7% of the mass of allyl alcohol glycidyl ether; In step S4, the epoxy resin is bisphenol A epoxy resin; the mass ratio of the epoxy resin modifier to the epoxy resin is 2-4:96-98; In step S5, the epoxy resin curing agent is polyamide 651, and the mass ratio of the epoxy resin curing agent to the product of step S4 is 35-50:50-65.
2. The super-tough epoxy steel slag asphalt mixture according to claim 1, characterized in that: The basalt aggregate includes basalt No. 1 material with a particle size of 10-15mm, basalt No. 2 material with a particle size of 5-10mm, and basalt No. 3 material with a particle size of 0-5mm; the mass ratio of basalt No. 1 material, basalt No. 2 material, and basalt No. 3 material is 14-17:9-12:38-42.
3. The super-tough epoxy steel slag asphalt mixture according to claim 1, characterized in that: The steel slag coarse aggregate is converter steel slag or electric furnace steel slag, including steel slag No. 1 material with a particle size of 10-15mm and steel slag No. 2 material with a particle size of 5-10mm. The mass ratio of steel slag No. 1 material to steel slag No. 2 material is 20-22:13-16.
4. The super-tough epoxy steel slag asphalt mixture according to claim 1, characterized in that: The particle size of the mineral powder filler is not greater than 6 mm.
5. The super-tough epoxy steel slag asphalt mixture according to claim 1, characterized in that: The SBS modified asphalt type is any one of type IA, type IB, type IC or type ID.
6. The super-tough epoxy steel slag asphalt mixture according to claim 1, characterized in that: The fiber is basalt fiber or lignin fiber.
Citation Information
Patent Citations
Epoxy asphalt mastic macadam mixture suitable for airfield pavement and preparation method thereof
CN111574109A
Steel slag asphalt mixture and preparation method thereof
CN113563010A
Epoxy emulsified asphalt mixture containing steel slag as well as preparation method and use method of epoxy emulsified asphalt mixture
CN113603399A
Low-activity steel slag asphalt mixture and preparation method thereof
CN114213060A
Preparation method of hydrogenated epoxy resin modified emulsified asphalt
CN116178975A